Empowering Cihideung Village Farmers in Using Rose Flowers as Pharmaceutical Raw Materials - Santun Bhekti Rahimah; Herry S. Sastramihardja; MIranti Kania Dewi; Siti Annisa Devi Trusda; Yuke Andriane (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Roses (Rosa Damascene Mill) are the most prominent crops of the Cihideung Village community. During the COVID-19 pandemic, flower farmers needed help with marketing, so many of the roses were unused. These empowerment activities aim to increase the public's knowledge and capacity to use roses as a pharmaceutical. The activities are carried out offline in the form of workshops. The raw materials are fresh rose flowers, tools, ingredients for making rose water infusions, soap, and oil. Analysis of outcome was assessed using questionnaires before and after the workshop as well as observation of the enthusiasm of participants during the activity. The results showed an improvement in the knowledge and skills of the public regarding the use of roses. The community also provided guides for the improvement of their capacity independently and access to the technical video through YouTube. Activity publications are delivered in digital media as a promotion. The full support of the provincial government and local villages will strengthen the synergy and sustainability of these activities, and hopefully, in the future, this knowledge can improve and become an independent enterprise of the community of Cihideung Villages.